THE PREVALENCE OF LOW ANTERIOR RESECTION SYNDROME IN RECTAL CANCER PATIENTS WHO UNDERWENT SURGICAL TREATMENT IN ISFAHAN CITY HOSPITAL DURING 2012-2018 - Sanei, Behnam; Ghasemi Fard, Mohammad; Kolahduzan, Mohsen (Medicinski časopis, 2020)
Objective. We aimed to determine the relative frequency of low anterior resection syndrome (LARS) in patients with rectal cancers who underwent surgical treatment in Isfahan. Methods. We evaluated all patients who referred to the surgery clinic of Saint Al-Zahra hospital in Isfahan within six years. After identifications, if LARS, according to the LARS score tool, the frequency of resection complications, factors affecting the LARS, morbidity, and mortality, the frequency distribution of defecation, stool consistency, and rate of significant improvement was evaluated. Results. Fifty-two patients were evaluated. The prevalence of LARS was 78.8%. Postoperative fecal and gas incontinence, clustering, fecal frequency, and fecal urgency in LARS patients were significantly higher than patients without LARS (P<0.05). There was no significant difference between the two groups in terms of factors affecting the LARS (p<0.05). In most of the patients with LARS, the defecation frequency was more than seven times a week (82.1%), and they mostly had liquid stool (61.5%). 95.5%. Of the patients with LARS showed significant improvement, which was mostly after 11-7 months (38.5). There was a significant difference between the frequency distribution of defecation, stool consistency, and significant improvement status in patients with and without LARS. Conclusion. LARS occurs commonly among patients undergoing LAR with TME and is associated with more resection complications. Patients with LARS have a significantly higher frequency of defecation per week and liquid stools and mostly achieve significant improvements. Other factors might not be significantly different between patients with or without LARS.